THE APPLICATION OF VON BERTALANFFY GROWTH CURVE ON THE DEMOGRAPHIC STUCTURE OF BIVALVAE POPULATIONS AT REMBANG WATER, CENTAL JAVA - Muhammad Zainuri (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The determination of bivalvae demographic structure were conducted in Rembang Waters, central Java. The samples were collected and observed in situ, from February to May, 1996 and coverd 3 species, which are Mactra sp., Solen sp. and Pholas sp. The Von bertalanffy Growth Curve allows the determination of bivalvae population growth and their evolution. This is in regard to their presence according to sampling time and their abundances. The growth model was adjusted by several approaches, using the computer program, called DATAX . It was found that, the general pattern of bivalvae demographic structure was directly related to the ecological capacity and hydrodynamic factors of sampling area.